2012
DOI: 10.2533/chimia.2012.187
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Iridium-Catalyzed Asymmetric Hydrogenation: New Catalysts, Substrates and Applications in Total Synthesis

Abstract: Iridium-catalyzed asymmetric hydrogenation has emerged as a highly efficient method for the synthesis of enantiomerically pure compounds. This account summarizes our recent efforts in this field. We have developed a new type of P, O-ligand that was successfully applied to the asymmetric hydrogenation of α,β-unsaturated carbonyl compounds. Furthermore we have demonstrated the potential of known iridium catalysts in the hydrogenation of α,β-unsaturated boronic esters. And finally we could demonstrate the utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It is easy to hydrogenate substrates D with relatively high enantiomeric excesses using chiral analogs of Crabtree’s catalyst. For instance, Pfaltz’s group alone have published at least 18 research papers (excluding reviews) that feature hydrogenation of this particular substrate. , Figure shows some of the ligands that have been used to do this, the particular ester involved, and the enantiomeric excesses obtained. Figure shows ligands that Andersson’s group have used in similar hydrogenations. , Stereoselectivities in these reactions are relatively tolerant of simple changes to the ester–alkyl functionality, and high conversions are the norm (Figure ).…”
Section: Carboxylate Estersmentioning
confidence: 99%
“…It is easy to hydrogenate substrates D with relatively high enantiomeric excesses using chiral analogs of Crabtree’s catalyst. For instance, Pfaltz’s group alone have published at least 18 research papers (excluding reviews) that feature hydrogenation of this particular substrate. , Figure shows some of the ligands that have been used to do this, the particular ester involved, and the enantiomeric excesses obtained. Figure shows ligands that Andersson’s group have used in similar hydrogenations. , Stereoselectivities in these reactions are relatively tolerant of simple changes to the ester–alkyl functionality, and high conversions are the norm (Figure ).…”
Section: Carboxylate Estersmentioning
confidence: 99%
“…1,11 It is also known that, in catalytic processes involving cationic complexes, the nature of the anion can have a marked influence on the rate and stereoselectivity of reactions. [12][13][14][15][16][17][18][19][20][21][22] However, although numerous electrochemical studies have demonstrated that the nature of the supporting electrolyte anion has an influence on the redox behaviour of compounds bearing (several) oxidisable ferrocenyl units, [23][24][25][26][27][28][29][30][31] the influence of the anion in redox-switchable catalysis involving ferrocenyl ligands has seldom been investigated. 31,32 This can be explained by the fact that most previously reported systems describe an ''on-off'' behaviour upon oxidation of the ferrocenyl unit, where the nature of the anion may not be crucial.…”
Section: Introductionmentioning
confidence: 99%